Effect of interactive media, make a match and lecture method on learning virus achievement - Agus Ariyanto; Wahyu Hari Kristiyanto; Rully Adi Nugroho (Biosfer: Jurnal Pendidikan Biologi, 2021)
The study investigates the effect of interactive media, make a match, and lecture method on learning achievement of virus. The research method used was quasi-experimental (quasi-experimental) with the pretest-posttest non-equivalent control group design. This research was conducted from September 2019 to November 2019 in High School A and High School T with a duration of learning ± 3 hours of study.ANOVA test results on the average value of N-Gain showed the same results as the post-test. N-Gain in ICT learning media class, make a match learning model class and lecture learning method classes respectively amounted to 58.6 ± 13.6, 40.8 ± 17.6 and 40.5 ± 14.3. However, based on linear regression analysis, student learning outcomes are influenced by student perception factors and students' visual learning styles (P <0.05). The successful use of interactive ICT learning media is influenced by student perception factors and student visual learning style factors.